Nonlinear dynamics of a conical dielectric elastomer oscillator with switchable mono to bi-stability - Cao, Chongjing; Hill, Thomas L.; Li, Bo; Wang, Lei; Gao, Xing (International journal of solids and structures, 2021)
Dielectric elastomer actuators (DEAs) are an emerging type of soft actuator that show many advantages including large actuation strains, high energy density and high theoretical efficiency. Due to the inherent elasticity, such actuators can also be used as soft oscillators and, when at resonance, the dielectric elastomer oscillators (DEOs) can exhibit a peak oscillation amplitude and power output with an improved energy efficiency in comparison to non-resonant behaviour. However, most existing DEOs have a fixed pre-defined morphology and demonstrate a single stable equilibrium, which limits their versatility. In this work, a conical DEO is proposed which may exhibit either monostability (i.e. one stable equilibrium point) or bistability (two equilibria). The system demonstrates a transition between two regimes using a voltage control. Such a feature allows the DEO system to have multiple oscillation modes with different equilibrium points and the transition between equilibria is controlled by an effective control strategy proposed in this work. A mathematical model based on the Euler-Lagrange method is developed to investigate the stability of this system and its complex nonlinear dynamic response in unforced and parametrically forced cases. This design has potential in more advanced and versatile DEO applications such as active vibrational controllers/ shakers, active morphing structures, smart energy harvesting and highly programmable robotic locomotion.